Morphometry and Relative Growth of Populations of Tanais dulongii (Audoin, 1826) (Tanaidacea: Tanaidae) in Pristine and Impacted Marine Environments of the Southwestern Atlantic - Rumbold, Carlos Enrique (2014)
Life history strategies are closely related to environmental conditions and biotic and abiotic factors play a major role conditioning several traits as growth rates, sexual maturity, size and morphometric differences. We compare body dimensions, relative growth patterns, and size of sexual differentiation between populations of Tanais dulongii (Audoin, 1826) that live in two contrasting habitats in order to determine if they differ in life history traits. Some 900 individuals were collected (150 males, 150 females and 150 juveniles from each site) in a rocky shore with a lower anthropic impact (La Estafeta) and a polluted area (Mar del Plata Harbor) and thirteen body dimensions between sexes and environments were compared. Relative growth rates were determined establishing the relationship between total length (TL) and the rest of body dimensions with reduced major axis method (RMA). Regression slopes were employed to test the degree of isometry or allometry. MDS and SIMPER analyses were used to plot and identify morphometric differences between sexes and populations. TL and the rest of body dimensions were longer in La Estafeta than in Mar del Plata, and degree of sexual differentiation was larger in La Estafeta (ca. 3.5 mm) than in Mar del Plata (1.75 mm). RMA showed differences among sites: in Mar del Plata growth of most dimensions was positively allometric in adults, but in La Estafeta half of the measured dimensions had positive allometric growth for both sexes and half had isometric or negative allometric growth. Juveniles of both sites showed a positively allometric growth. MDS established a clear separation between sites and sexes. SIMPER showed that TL, cheliped length, cheliped width, and antennule peduncle length contributed most to differences between sexes, and TL (mainly) and the rest of variables (in minor degree) in the dissimilarities between sites. We believe that the differences observed between populations of T. dulongii are due to phenotypic plasticity in this species in response to environmental differences.